Silvoarable agroforestry - Beaton, A.; Incoll, L. D.; Burgess, Paul J. (The Royal Scottish Forestry Society, 1999)
Introduction: A silvoarable system of land management implies the cultivation of trees and arable crops on the same area of land, a system practised quite commonly in southern Europe and in the tropics. The system comprises two components: tree rows, generally one tree wide, and arable alleys, alternating across the field. The first major development of silvoarable practice in the UK took place during the 1960s and 1970s when Bryant & May established extensive poplar plantations on lowland farmland in southern England to supply their own market for match veneer timber (Beaton, 1987). Since the demise of the Bryant Sr May market for match timber in 1978, interest in the potential for silvoarable systems lay dormant until the advent of food crop surpluses in the 1980s.
Keywords: Silvoarable; Agroforestry; Poplar